Exploring fungal and viral pathogens associated with intermediate wheatgrass, a promising new small grain crop - Webb, Griffin; Tidakbi, Lawrence; Bruce, Myron; Rupp, Jessica (My University, 2023)
Small grain production in Kansas and other states in the central United States is a crucial component of agricultural economies. One emerging small grain is Kernza®, the grain harvested from intermediate wheatgrass (IWG, Thinopyrum intermedium). This crop is a perennial grass in contrast to common annual wheat varieties grown worldwide. This aspect of IWG allows it to develop a large root structure which provides soil structure and prevents the need for yearly tillage. With its recent emergence, however, there is little data available about the susceptibility of Kernza® to common small grain diseases. We are collecting and analyzing samples of Kernza® from growers to identify pathogens, with a special focus on Fusarium head blight (FHB). We cultured 29 samples by surface disinfesting grains, then incubating them on Spezieller Nahrstoffarmer Agar (SNA). The nutrient composition of SNA encourages growth of Fusarium spp. The resulting cultures were then used for DNA analysis to determine the species of fungi present. Additionally, 22 leaf samples obtained from growers were subjected to DAS-ELISA to determine if intermediate wheatgrass can be infected with wheat streak mosaic virus, a common viral pathogen of wheat. Our results indicate that Kernza® is susceptible to both FHB and wheat streak mosaic virus. Growers looking to plant Kernza® should be aware of these potential pathogens and take appropriate action to mitigate potential yield loss. Further investigation regarding the potential of other pathogens that could infect IWG is necessary.
Keywords: Intermediate wheat grass; Kernza®; Fusarium head blight; WSMV; ELISA; USDA NIFA 2019-67032-29071